A Feasibility Study on the Composting of Kitchen and Yard Wastes of Quezon City - Banda, Lota; De Celis, Excel Ann.; Ventura, Jonathan (Diliman, Quezon City College of Engineering, 2001)
Recent updates on solid waste management practices in the country showed that there is a growing concern to phase out all open dumpsites in the country owing to grave threat to public health and the environment. With the 6000 tons of garbage generated in Metro Manila daily, no landfill will sustain the disposal of such huge amount of wastes. Worldwide, incineration technologies and landfills are being phased out towards the more environmentally sound recycling and composting. Currently, the effects of pollution and the conventional waste disposal into landfills are real issues calling for the attention of society and it is high time for the government to seriously consider the large scale conversion of wastes to organic fertilizers. This paper presents the project feasibility of composting the compostable portion of the wastes generated by Quezon City, which comprise 20% of the total wastes generated by Metro Manila. The market, technical, and social profitability of the project is investigated thoroughly to come up with the implementation decisions on the composting project. The market for the organic fertilizer or compost showed a large demand for the product owing to its properties of being low-priced, and acting as a supplement to inorganic fertilizers in increasing crop production and minimizing soil erosion. Considering the present supply for the product, the demand-supply trends show that there is a great opportunity to penetrate the organic fertilizer industry through the composting of wastes. To satisfy the identified supply-demand gap for the product, a total of 23 barangays in Quezon City are identified, each will have its own composting facility and a defined waste collection and production systems. Local technologies will be utilized after comparing with other available technologies abroad and from related literature reviews. The complexity and level of technology or mechanization and automation were the primary criteria used in selecting the operational components of the system. The overall system for the actual construction, operation, and sustaining the technical requirements of the composting project can be implemented with a high level of efficiency. After determining the total project cost, the financing and economic profitability requirements of the project to be considered acceptable is evaluated. The total financing for the project can be provided for and will come from two sources: from the newly created corporation's shareholder's equity, and from loans provided by commercial banks. Further, incentives can be availed of from the Board of Investments as the project can be classified into one of their priority project categories. Donated capital in terms of land or building is also solicited from the City government and the barangays. In securing the profitability of the project after starting its operations and to guarantee the planning period are made. Financial indicators such as the IRR, NPV, and additional break-even and sensitivity analysis for the other relevant profitability measures proved the financial profitability of the project. After evaluating the project in terms of its feasibility in the market, technical, financial and social profitability studies conducted, the ?Composting of Quezon City Kitchen and Yard Wastes? project is feasible and can be implemented.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Yard waste; Compost; Participatory monitoring and evaluation (Project management)